Effectiveness of splinting for pain and function in people with thumb carpometacarpal osteoarthritis: a systematic review with meta-analysis. Issue 4 (April 2019) - Buhler, M.; Chapple, C.M.; Stebbings, S.; Sangelaji, B.; Baxter, G.D.
Summary: Objective: To examine the effectiveness of splinting for reducing pain and improving function and health-related quality of life (HR-QoL) in people with thumb carpometacarpal osteoarthritis (CMC OA). Design: The Cochrane Library, MEDLINE, Embase, CINAHL, ISI Web of Science, Scopus and Google Scholar, 3 trial registries and 4 conference proceedings were systematically searched for randomised and non-randomised controlled trials up to March 17th, 2018. Two reviewers independently applied the inclusion criteria to select potential studies and assess risk of methodologic bias using the Cochrane Collaboration's Risk of Bias Tool. Studies were pooled using the inverse variance method to calculate standardised mean difference (SMD). Sensitivity analyses were conducted and the quality of evidence for each outcome was judged following the Grades of Recommendation Assessment, Development and Evaluation (GRADE) approach. Results: Twelve studies were retrieved ( n = 1353), 4 comparing a splint to control and 8 to another splint. In the medium-term (3–12 months), low quality evidence showed that splints cause a moderate to large reduction in pain (SMD 0.7 [95% confidence interval (CI) 1.04, 0.35], P < 0.0001) and small to moderate improvement in function (SMD 0.42 [95% CI 0.77, 0.08], P = 0.02). No significant effect was found at short-term or for different types of splints. No studies reported HR-QoL. Conclusions: Splinting demonstrated a moderate to large effect for pain and small to moderate effect for function in the medium-term but not in the short term. Quality of the evidence is low. Major challenges are the lack of diagnostic criteria and of a gold-standard outcome measure for thumb CMC OA.